Collective awareness and self-awareness in the teaching / learning of French as a second language and the language of schooling: when interculturality and plurilingualism are at stake - Auger, Nathalie (Glottodidactica, 2022)
This article explores the issue of the collective consciousness and self-consciousness in teaching and learning foreign languages. A review of the literature on the current issues of interculturality and plurilingualism in relation to the notions of consciousness and self-consciousness is first detailed. The issue raised allows us to question the impact of this consideration in terms of the consequences of this work on class dynamics. In fact, can the awareness and self-awareness of learners regarding intercultural and plurilingual practices exist outside of a co-construction with other learners, with the teacher? The research methodology is based on an analysis of interactions in the language class which brings into play these intercultural and plurilingual approaches (resulting from the LISTIAC and FLSCAN projects). It reports significant results on the co-construction of consciousness and emerging self-consciousness in the language class about the singular universals of languages and cultures. The discussion shows the value of a collective, and no longer purely personal understanding (for the learner) of consciousness and self-awareness of these plurilingual and cultural experiences.